Integration of Entrepreneurship Learning Models in Improving Students' Interest and Competence: A Systematic Literature Review: Entrepreneurship Learning Models - Flora Puspita (Escalate : Economics and Business Journal, 2026)
Entrepreneurship education plays a strategic role in fostering students' entrepreneurial interest and competency amidst economic challenges and technological development. This article aims to systematically examine various entrepreneurship learning models and their contribution to enhancing students' entrepreneurial interest and competency. The research method used was a systematic literature review (SLR) of 15 national and international scientific articles published between 2018 and 2025. The selection process involved identifying, screening, and analyzing articles based on topic relevance and publication quality. The study's findings indicate that experiential, collaborative, and contextual entrepreneurship learning models, such as experiential learning, project-based learning, and gamified learning, are more effective in developing attitudes, self-efficacy, creativity, and entrepreneurial readiness. Furthermore, technology integration and support from a learning ecosystem contribute to the holistic development of entrepreneurial competency. In conclusion, entrepreneurship education, designed in an integrated and sustainable manner, has the potential to produce a generation of entrepreneurs who are adaptive, ethical, and capable of contributing to sustainable economic and social development.